NURSES' CARING BEHAVIOR AND PATIENTS' FAMILY ANXIETY LEVELS IN THE INTENSIVE CARE UNIT - Deddy Adi Wirawan; Edy Soesanto; Yulisetyaningrum Yulisetyaningrum ((IJP) Indonesia Jurnal Perawat, 2025)
The Intensive Care Unit (ICU) is a specialized area in hospitals where critically ill or injured patients receive specialized and intensive nursing care. In this setting, family members of patients often feel less involved in their care and are unable to accompany them in the ICU, leading to anxiety. This study aims to investigate the relationship between nurses' caring behavior and family anxiety in patients treated in the ICU of RSU PKU Muhammadiyah Banjarnegara. The population of this study consists of 83 people, with a sample size of 45 people. The sampling technique used is Purposive Sampling. This study uses an analytical correlational design with a cross-sectional approach. This study utilized the Caring Assessment Tools questionnaire and the Hamilton Anxiety Rating Scale (HARS) as research instruments. The results revealed a significant correlation between caring behaviors and family anxiety, with a p-value of 0.000. Based on these findings, it is recommended that nurses implement caring behaviors towards patient families to mitigate excessive anxiety related to the patient's condition